Remaining controversies in the upfront management of advanced ovarian cancer. Issue 5 (1st August 2004) - Mano, M. S.; Awada, A.; Minisini, A.; Atalay, G.; Lago, L. D.; Cardoso, F.; Piccart, M.
Abstract : Ovarian cancer (OC) is one of the leading causes of cancer-related death in women. In the last decades, a lot of energy and resources have been put into a number of clinical trials, with some success. Nevertheless, the prognosis of patients diagnosed with advanced disease remains extremely poor. As research moved forward, some crucial questions with regard to the optimal upfront management of patients with advanced OC (AOC) have remained unanswered. In this article, we review the rationale behind these controversial issues, and provide the levels of evidence supporting the current recommendations for AOC management.